Synthesis and structure of some azolium salts - Thong, Pham Van; Hien, Nguyen; Ha, Nguyen Son; Thanh Chi, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
The reactions between benzimidazole, imidazole, or 1,2,4-triazole with either benzyl chloride or isopropyl bromide yielded 6 azolium salts, namely 1,3-dibenzylimidazolium chloride (M1), 1,3-dibenzylbenzimidazolium chloride (M2), 1,3-dibenzyl-1,2,4-triazolium chloride (M3), 1,3-diisopropylimidazolium bromide (M4), 1,3-diisopropylbenzimidazolium bromide (M5), and 1,3-diisopropyl-1,2,4-triazolium bromide (M6). These salts can be further used as the starting compounds for the synthesis of complexes based on N-heterocyclic carbenes for various applications. The structures of M1÷M6 have been unambiguously determined by means of IR and 1H NMR spectroscopic methods. Keywords. N-heterocyclic carbenes, azoles, azolium salts.